Region-specific and activity-dependent regulation of SVZ neurogenesis and recovery after stroke - Liang, Huixuan (Proc Natl Acad Sci U S A, 2019)
Stroke is the leading cause of adult disability. Neurogenesis after stroke is associated with repair; however, the mechanisms regulating poststroke neurogenesis and its functional effect remain unclear. Here, we investigate multiple mechanistic routes of induced neurogenesis in the poststroke brain, using both a forelimb overuse manipulation that models a clinical neurorehabilitation paradigm, as well as local manipulation of cellular activity in the peri-infarct cortex. Increased activity in the forelimb peri-infarct cortex via either modulation drives increased subventricular zone (SVZ) progenitor proliferation, migration, and neuronal maturation in peri-infarct cortex. This effect is sensitive to competition from neighboring brain regions. By using orthogonal tract tracing and rabies virus approaches in transgenic SVZ-lineage-tracing mice, SVZ-derived neurons synaptically integrate into the peri-infarct cortex; these effects are enhanced with forelimb overuse. Synaptic transmission from these newborn SVZ-derived neurons is critical for spontaneous recovery after stroke, as tetanus neurotoxin silencing specifically of the SVZ-derived neurons disrupts the formation of these synaptic connections and hinders functional recovery after stroke. SVZ-derived neurogenesis after stroke is activity-dependent, region-specific, and sensitive to modulation, and the synaptic connections formed by these newborn cells are functionally critical for poststroke recovery.